2011
DOI: 10.1016/j.jhazmat.2011.04.078
|View full text |Cite
|
Sign up to set email alerts
|

Predictive hydrogeochemical modelling of bauxite residue sand in field conditions

Abstract: >Geochemical and hydrological model for bauxite residue sand. >Combined hydrogeochemical simulation of bauxite residue sand under field conditions, in 2D, heterogeneous domomain. >Evaluation of management practise for the amelioration of bauxite residue sand as substrate for plant growth.This manuscript illustrates an innovative application of detailed hydrogeochemical modelling to the field of bauxite residue management. A recently developed simulation tool that combines geochemical reaction calculations in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 68 publications
2
7
0
Order By: Relevance
“…9) only exhibit a narrow section. This neutralizing behavior is associated with the dissolution of sodalite, tricalcium aluminate, calcite and other alkaline compounds (Snars and Gilkes, 2009;Wissmeier et al, 2011). This tendency may demonstrate that fresh bauxite residue contains a larger concentration of sodalite, tricalcium aluminate and calcite, compared to aged residues (consistent with Fig.…”
Section: Transformation Of Acid Neutralizing Capacitysupporting
confidence: 75%
See 1 more Smart Citation
“…9) only exhibit a narrow section. This neutralizing behavior is associated with the dissolution of sodalite, tricalcium aluminate, calcite and other alkaline compounds (Snars and Gilkes, 2009;Wissmeier et al, 2011). This tendency may demonstrate that fresh bauxite residue contains a larger concentration of sodalite, tricalcium aluminate and calcite, compared to aged residues (consistent with Fig.…”
Section: Transformation Of Acid Neutralizing Capacitysupporting
confidence: 75%
“…Much of this neutralizing behavior is associated with hydroxyls on the surfaces of iron oxides (FeO,its reaction (Eq. (11) occurs at the region of pH<6) in the bauxite residue and dissolution of sodalite, 12), ( 13) and ( 14) (Snars and Gilkes, 2009;Wissmeier et al, 2011;. The length of the neutralizing region reflects the contents of these components in the bauxite residue.…”
Section: Transformation Of Acid Neutralizing Capacitymentioning
confidence: 99%
“…The water potential exceeded −1000 kPa (pF: 4) during long-term drought conditions (lack of intense rainfall events) (Figure 4). In this context, Wissmeier et al [51] reported that the water potential of residue sand obtained from bauxite residue did not drop below −1500 kPa (pF: 4.17) during drought conditions (periods with lack of sufficient rainfall). In our study, the high clay and silt content of the bauxite residue (i.e., fine texture of bauxite residue) affected its hydraulic parameters (i.e., high residual water content and low hydraulic conductivity) (Tables 1 and 2), and thus led to the low infiltration of water to deeper depths of the profiles.…”
Section: Application Of Hydrus-1d Modelling For Management Of a Bauximentioning
confidence: 99%
“…The module fully implements all of the capabilities of the general‐purpose geochemical reaction model PHREEQC (Parkhurst and Appelo ), including temperature‐dependent interactions between water and minerals, gases, ion exchangers, surface complexers, and solid solutions. The capability for users to define reactants and kinetic rate expressions allows PHREEQC to be used for simulating a wide range of biogeochemical processes, such as geologic sequestration of carbon dioxide (Garcia‐Rios et al ), transport of arsenic in the environment (Campbell and Nordstrom ), acid mine drainage (Shim et al ), fate of residues from mining and mineral processing (Wissmeier et al ), and impacts of agricultural practices on groundwater quality (Ledesma‐Ruiz et al ).…”
Section: Approachmentioning
confidence: 99%